Performance and interpretation of spirometry among Swedish hospitals. (27th January 2015) - Belfrage, Björn; Hansson, Anders; Bake, Björn
Abstract: Background and Aims: It is unclear to what extent spirometric performance and interpretation is standardized in Sweden. The aim of this study was to find out how spirometry is performed and interpreted in large Swedish hospitals. Methods: In telephone interviews, technicians and physicians working with lung function measurements at 21 large Swedish hospitals were interviewed about routines for spirometry. Results: Answers were obtained from 37 of the 42 departments contacted revealing differences in the spirometric routines. Some departments lack a written method description, and three different prediction equations were used among the departments. Different ways of calculating the forced expiratory volume in 1 s (FEV1)/vital capacity (VC) ratio (FEV%) were found and also differences in performance and interpretation of the reversibility test. When diagnosing chronic obstructive pulmonary disease, none of the departments reported using an individualized diagnostic limit of FEV1/VC based on age, sex and height. Conclusion: There is a need for standardization of performance and interpretation of the spirometry test in Sweden and probably also in other countries.